Image Encryption Using DNA Encoding and RC4 Algorithm - Hameed, Sarab M.; Sa’adoon, Hiba A.; Al-Ani, Mayyadah (Iraqi Journal of Science, 2018)
Nowadays, the rapid development of multi-media technology and digital images transmission by the Internet leads the digital images to be exposed to several attacks in the transmission process. Therefore, protection of digital images become increasingly important. To this end, an image encryption method that adopts Rivest Cipher (RC4) and Deoxyribonucleic Acid (DNA) encoding to increase the secrecy and randomness of the image without affecting its quality is proposed. The Means Square Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Coefficient Correlation (CC) and histogram analysis are used as an evaluation metrics to evaluate the performance of the proposed method. The results indicate that the proposed method is secure against statistical attacks and provides a good security without affecting the quality of the image.